If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -9y + 6x + 3y + -2x = 0 Reorder the terms: 4x + 6x + -2x + -9y + 3y = 0 Combine like terms: 4x + 6x = 10x 10x + -2x + -9y + 3y = 0 Combine like terms: 10x + -2x = 8x 8x + -9y + 3y = 0 Combine like terms: -9y + 3y = -6y 8x + -6y = 0 Solving 8x + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 8x + -6y + 6y = 0 + 6y Combine like terms: -6y + 6y = 0 8x + 0 = 0 + 6y 8x = 0 + 6y Remove the zero: 8x = 6y Divide each side by '8'. x = 0.75y Simplifying x = 0.75y
| 3(2x-6)-(2x+1)=9 | | 2x+1=3(x-1) | | 5x-3x=x+9 | | 8n=5n+39 | | 7.4=w-3.9 | | 33=7(w+7)-3w | | n-37=0 | | 150=v+113 | | sqrt(x+1)-sqrt(9-x)=sqrt(2x-12) | | -10g^2+13g-4=0 | | 2sin^2(4x)-1=0 | | -10g+13g-4=0 | | 3x+2*2x=21 | | 3.4=3p | | 9v=ir | | 3(x-8)=-9x+12 | | 10t-11=7t-5 | | 3.3x-11.26=5.9 | | -6x-2=(3x^2+1) | | 180=28x+(x*x) | | X(4X-8)=(4X+5)(x-2) | | 9+(9+x)+(9+.5(9+x))=9+(9+x)+(9+.5(9+x)) | | 3(x+5)=2(4x+10) | | 2(x-2)=60-(1-x) | | 14=0.8x | | 3x+3x+4x-30=180 | | 5y(2x-1)=y(x+2)+20 | | 2.9x-18.31=7.5 | | x^2+22x-40=0 | | 2.2x-15.18=3.3 | | 7m-4-2m=13 | | 3.5=3(4+.5r) |